Nationalism, Citizenship Identity, Public Opinion Construction, and Social Control in TribunNews Coverage of the LPDP Student Citizenship Controversy: A Framing Analysis Using Robert N. Entman's Model - Eva Kusnul Hidayah; Khusnul Khotimah; Yusfandri Yusfandri; Amalia Sabrina Pawestri; Malik Ibrahim (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze how TribunNews constructs the controversy surrounding LPDP alumna Dwi Sasetyaningtyas regarding her child’s citizenship status and to identify the dominant framing patterns used in shaping public perceptions of nationalism, citizenship identity, and public opinion. Methodology: This study employed a qualitative approach using Robert N. Entman’s framing analysis model. The data consisted of 16 purposively selected news articles published by the TribunNews network between 22–28 February 2026. Data were collected through digital searches, observation, and documentation, and analyzed using Entman’s four framing elements. To enhance research credibility, the study applied an audit trail, peer checking, and expert validation. Main Findings: This study extends the application of Robert N. Entman's framing model by identifying the dynamic evolution of media framing in a citizenship controversy. It contributes to communication and social science studies by demonstrating how media framing functions not only as a representation of events but also as a mechanism for constructing nationalism, citizenship identity, public opinion, and collective social norms. Novelty/Originality of this study: This study is the first to examine TribunNews' framing of the LPDP student issue in the controversy over the citizenship status of children using Entman's model. This novelty expands the application of framing theory in the realm of sovereignty and national loyalty, which has never been studied before.